Pembatalan Perkawinan Sepersusuan Akibat Ketidaktahuan Kedua Mempelai Berdasarkan Hukum Perdata dan Kompilasi Hukum Islam - Patricia, Andi Yohani; Chandra, Irgi Fahreza; Nasution, Kumala Sari; Hasan, Miftahul; Sitorus, Purnama Manda; Hannum, Syarifah; Yulita, Tengku Bebita (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2023)
In Islam, marriages carried out due to blood relations or mahrams are automatically considered to have never existed and are invalid even though husband and wife have had intercourse. The marriage was canceled by itself because there was a prohibition and the pillars and conditions for a valid marriage were not fulfilled which caused the marriage to be annulled. The method used is Normative Juridical, which aims to know and understand the arrangements for the Compilation of Islamic law regarding same-breeding marriages without the knowledge of the bride and groom and how to resolve disputes over the cancellation of breastfeeding marriages due to ignorance. The legal material used comes from legislation and sources of Islamic law. Because in discussing the problems in this study. Article 8 paragraph 4 of the law on marriage states that there is a prohibition on marriage between two people who are related to breastfeeding, namely children who are breastfed, siblings, aunts or uncles. If the marriage takes place but there is a prohibition or conditions are not met, then the marriage is cancelled. In this case, the process of canceling a marriage has a method in which the party who feels aggrieved submits their case to court if a breastfeeding marriage occurs without the knowledge of the bride and groom, then it is obligatory to cancel the marriage, because it is very clear that Islam prohibits breast-feeding. Keywords : breastfeeding, civil law, compilation of islamic law.